Fear of Covid-19 in Fitness Centers - H. Mehmet Tunçkol, Tolga Şahin, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The fitness centers are the places which people can do exercise for their physical fitness, subjective wellbeing and health. These places should have suitable conditions like ventilation system, locker rooms, hygiene etc. But in the period of Covid-19 pandemic, air conditions, locker rooms and hygiene procedures couldn’t solve the infections wide spreading. Then the situation went worst and precautions like lockdowns, shut downs and curfews came in our life. In this period, people have fear of Covid-19 all over the world. After the lockdowns, shut downs and curfews people still have fear of Covid-19. Aim: The aim of this study is to determine the fear of Covid-19 in thorough the fitness center members in the process of normalization. Material and Methods: This study utilized the survey method that is used most commonly in descriptive research models. In the survey method, samples consist of large groups, and each member of the group is asked about own opinions in order to learn attitudes on a case, fact or a situation. For determining the fear level a survey applied to subjects consisted from Personal Data Form and “Fear of Covid-19” Scale. The study group is consisted from 394 individuals who have valid memberships in different sizes of fitness centers. Results: After the analysis, normal distribution of the data was examined according to the values of skewness and kurtosis. Further analysis showed that members having mid-level (mean=16,33) fear of Covid-19. And also there’s significant difference according to age and place of residence variables. Conclusion: More countries should take into consideration to understand how the pandemic of Covid-19 affects fear levels of fitness center members globally. Also it could be recommended to prevention programs to members for help to overcome fear of Covid-19.